Perbedaan tingkat kebersihan rongga mulut pada mahasiswa kedokteran gigi dengan mahasiswa kedokteran umum di Fakultas Kedokteran Universitas Udayana - Ketut Gde Rai Wijaya; Putu Lestari Sudirman; Luh Seri Ani (School of Dentistry Faculty of Medicine Udayana University, 2018)
Background: Oral cavity consists of teeth, gingiva, palate, tongue and other mucosal tissues. Maintaining oral health is important, and influenced by several factors, including body image, social practices, social and economic status, knowledge, cultural variables, as well as a personal choice. Objective: This study aims to investigate the differences of oral hygiene index level between dental and medical students. Methods: this was an analytic observational study with cross-sectional design. Subjects were 170 of dental and general medical students at Medical Faculty of Udayana University selected as the sample. The sampling technique used is the stratified random sampling. The level of oral hygiene is measured using a score OHI-S. Data obtained by clinical examination and questionnaires and then processed by computer software. Results: Based on the characteristics of age, gender, diet, and knowledge between dental dan general medical student get p-value > 0,05 and based on behavioral characteristic, general medical student with p-value < 0,05 whereas dental student with p-value > 0,05. Based on the characteristics of the majors, OHI-S of dental students were 90.6% and general medical students with OHI-S were 75.3% with p <0.05. Conclusions: There is a statistically significant difference in the level of oral hygiene between dental students and general medical students.